Lauren Briese: capstone - Briese, Lauren, artist (Colorado State University. Libraries, 2019)
The artist's statement: "Generating Texture" Texture is all around us. The ground we walk on is shaped by repetition of physical movements. When working with ceramics, touch - the impression of a fingertip - creates texture. These marks in the surface of the fired form will live in the world forever. Many ceramic surfaces are inspired by patterns in nature. My surfaces combine a texture made up of gestural pinched marks and textured glazes, that covers and explodes from the form. In my Ceramic Sculptures I think about both texture and scale. A large sculpture draws the eye towards the piece. Texture involves a dialogue between emotion and fluid movement. For me, texture is pure gesture. Gesture suggests freedom and fluidity that is both physical and emotional. When the scale of a piece is matched with a gestural surface treatment, the piece becomes an individual. As an artist, I have various intentions. I hope that viewers draw a range of connections from each piece. A viewer's opinion can influence future work. When I notice an association within a piece, I can further the idea or refrain from it. The texture and scale suggest a variety of mental images. These mental images allow me to understand the relationship between my hands, the clay, and my practice.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: pottery